PENGARUH PEMBELAJARAN PRAKTIK BERBANTUAN MEDIA AUDIO TERHADAP KEMAMPUAN MOTORIK DAN MOTIVASI BELAJAR SISWA SMP DI SLB A NEGERI DENPASAR - ., I GUSTI AYU DARIYATI; ., PROF. DR. A.A.ISTRI NGR.MARHAENI,M.A.; ., DR. NI KETUT WIDIARTINI, S.Pd.,M.Pd (Jurnal Penelitian dan Evaluasi Pendidikan Indonesia, 2015)
Penelitian ini bertujuan untuk mengetahui pengaruh pembelajaran praktik berbantuan media audio terhadap kemampuan motorik dan motivasi belajar siswa. Penelitian yang dilakukan adalah pretest-posttest design yang dilaksanakan di SLB A Negeri Denpasar. Subyek penelitian adalah siswa SMP yang berjumlah tujuh orang. Data kemampuan motorik dikumpulkan melalui lembar observasi dan motivasi belajar dikumpulkan melalui lembar kuesioner, dan data dianalisis menggunakan uji-t non-parametrik. Hasil penelitian menunjukkan (1) terdapat pengaruh pembelajaran praktik berbantuan media audio terhadap kemampuan motorik siswa (2) terdapat pengaruh pembelajaran praktik berbantuan media audio terhadap motivasi belajar.Kata Kunci : kemampuan motorik, motivasi belajar, pembelajaran praktik berbantuan media audio This research aims to investigate the effect of audio assisted learning method towards motor ability and learning motivation of junior high school students in SLB A Negeri Denpasar. Research design was pretest-posttest design. Sample in this research was the seven junior high school students in SLB A Negeri Denpasar. Motor ability data were collected using motor ability rubric, while learning motivation data were collected using learning motivation instrument. Data were then analyzed using non parametric t-test. T-test on motor ability shows that tobs = 2,938 > tcv = 2,447 (H0 is rejected and H1 is accepted). It means that there is a significant effect of audio assisted learning method on motor ability among junior high school students in SLB A Negeri Denpasar. T-test on learning motivation shows that tobs = 2,609 > tcv = 2,447 (H0 is rejected and H1 is accepted). This means that there is a significant effect of audio assisted learning method on learning motivation among junior high school students in SLB A Negeri Denpasar. In conclusion, the results show that: First, there is an effect of assisted learning method on students? motor ability. Second, there is an effect of assisted learning method on students? learning motivation among junior high school students in SLB A Negeri Denpasar academic year 2014/2015.keyword : audio assisted learning method, learning motivation, and motor ability